Portuguese EPBD based regulation put side by side with energy simulation tools - Silva, Pedro Correia Pereira da (2010)
In 2002 EU implemented the Energy Performance of Buildings Directive which led to the revision of the buildings thermal codes. The transposition of EBPD into the Portuguese legislation was made through three regulations: RCCTE for residential buildings, RSECE for office buildings and SCE that establishes the energy labelling system. The national code RCCTE sets two methodologies for assessing the energy performance of buildings: a simplified methodology and a more detailed one, depending if it is an existent or a new building. It has been observed that since the entrance into force of these codes, the project teams are using the RCCTE methodologies as tools to estimate the energy consumption of buildings. In this work it was tested the accuracy of this approach, performing two studies: one where the energy needs obtained with the RCCTE methodology were compared with the ones obtained with a dynamic simulation tool; and another where the same energy needs were compared with the ones obtained with a simplified RCCTE methodology foreseen for existing buildings. With the studies performed it was verified that the RCCTE methodology is accurate enough, except for the coldest regions, where another kind of tool should be applied. The simplified methodology showed inaccurate results and must be used with caution. However, with some corrections, important improvements can be achieved.